Electronic spreadsheets as a tool to support the decision in a company of the city of Pau dos Ferros – RN (Research, Society and Development, 2019)
With the informatization of companies and consequently with the arrival of Management Information Systems, greater control of business activities is possible, but not all companies use the system as a unique tool for management. In this way spreadsheets appear, which became great allies in this process of management and decision making. Thus, the present article aims to identify the importance of spreadsheets as administrative tools and to elaborate examples of its applications for the organization of the study. For methodological purposes, the bibliographic research was used, addressing the main concepts on the subject, and a case study that together resulted in the creation of solutions through spreadsheets. With this study, it was possible to show how spreadsheets are important for data control, which simplifies the information transformation process, considerably helping to control the flow of information occurring in the specific business environment, and with that, increases the manager's power to make decisions.